2016
DOI: 10.1186/s12888-016-1152-7
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomized controlled trial of a tailored cognitive behavioural therapy based intervention for depressive symptoms in those newly diagnosed with multiple sclerosis

Abstract: BackgroundTo examine the effectiveness and acceptability of an 8-week individual tailored cognitive behavioural therapy (CBT) intervention for the treatment of depressive symptoms in those newly diagnosed with multiple sclerosis.MethodsThe current study presents a pilot, parallel group randomized controlled trial (RCT) with an allocation ratio of 1:1 conducted in a large research and teaching hospital in Melbourne, Australia. 30 individuals with a mean age of 36.93 years (SD = 9.63) who were newly diagnosed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 38 publications
1
58
0
1
Order By: Relevance
“…The included studies were published between 2003 and 2017 and reported 11 RCTs ( 34 , 35 , 41 45 , 47 50 , 52 , 53 ), 4 pilot RCTs ( 40 , 43 , 46 , 55 ), 1 experimental and control groups pre-test/post-test pilot study ( 39 ), 1 observational study ( 56 , 57 ), 1 single group pre-test and post-test pilot study ( 54 ), and 2 single-group pre-test and post-test studies ( 33 , 51 ). The countries where the included studies took place were Turkey ( 33 ), the United States of America ( 41 , 45 ), Germany ( 42 ), Switzerland ( 53 ), Belgium ( 44 ), Australia ( 34 , 43 , 54 ), Italy ( 52 ), Iran ( 35 , 39 , 50 ), United Kingdom ( 40 , 46 48 , 51 ), Netherlands ( 56 , 57 ), and New Zealand ( 49 , 55 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies were published between 2003 and 2017 and reported 11 RCTs ( 34 , 35 , 41 45 , 47 50 , 52 , 53 ), 4 pilot RCTs ( 40 , 43 , 46 , 55 ), 1 experimental and control groups pre-test/post-test pilot study ( 39 ), 1 observational study ( 56 , 57 ), 1 single group pre-test and post-test pilot study ( 54 ), and 2 single-group pre-test and post-test studies ( 33 , 51 ). The countries where the included studies took place were Turkey ( 33 ), the United States of America ( 41 , 45 ), Germany ( 42 ), Switzerland ( 53 ), Belgium ( 44 ), Australia ( 34 , 43 , 54 ), Italy ( 52 ), Iran ( 35 , 39 , 50 ), United Kingdom ( 40 , 46 48 , 51 ), Netherlands ( 56 , 57 ), and New Zealand ( 49 , 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 16 included intervention and control studies, 10 studies ( 35 , 39 43 , 46 48 , 50 , 53 ) compared psychological interventions against non-active controls and 6 studies ( 34 , 44 , 45 , 49 , 52 , 55 ) compared psychological interventions against active controls. In four studies, two psychological interventions of interest were compared: CBT and supportive-expressive group (psychotherapy) ( 45 ); self-management occupational therapy (CBT) and relaxation therapy ( 44 ); and CBT and relaxation ( 49 ); and eye movement desensitization and reprocessing (EMDR) and relaxation therapy ( 52 ); respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It is unclear, however, whether the lack of effect is due to lack of uptake in the intervention because computerized sessions were incomplete for many patients (a median of one of the six sessions in MoodGYM completed and a median of two of the eight sessions in Beating the Blues completed). be highly effective in reducing depressive symptoms in patients with MS, [34][35][36] with one study suggesting that CBT may be as effective as pharmacotherapy. 37 In this study, patients with MS and depression were treated with weekly therapist-administered CBT, supportiveexpressive group psychotherapy, or sertraline (doses varying from 50-200 mg).…”
Section: Pharmacologic Treatmentmentioning
confidence: 99%
“…In fact, another study of small numbers of patients in the UK showed that CBT can be effective in routine clinical practice for MS patients with depression and anxiety. 21 In the present study, there was a possibility that the scores of thinking/fatigue of FAMS might be improved after the CBT intervention in some patients. As for QOL evaluated by FAMS, total scores increased after the fourth and the eighth sessions relative to baseline, although they were not statistically significant.…”
Section: Discussionmentioning
confidence: 62%
“…20 In contrast, there is another report of the effectiveness of CBT for improving depressive symptoms for the long term. 21 In the present study, there was a possibility that the scores of thinking/fatigue of FAMS might be improved after the CBT intervention in some patients. Further research is required to confirm the effects of CBT, and longer-term follow up to evaluate the effectiveness of CBT is required in future studies.…”
Section: Discussionmentioning
confidence: 62%